2021
DOI: 10.2147/cmar.s283952
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA Circ_0006282 Promotes Cell Proliferation and Metastasis in Gastric Cancer by Regulating MicroRNA-144-5p/Tyrosine 3-Monooxygenase/Tryptophan 5-Monooxygenase Activation Protein β Axis

Abstract: Background Circular RNAs (circRNAs) are a class of non-coding RNAs which function as novel regulators in human cancers. In this study, we aimed to investigate the functional roles and related molecular mechanisms of circ_0006282 in gastric cancer (GC) progression. Methods Fifty-five GC patients were enrolled in this study. GC cells (AGS and HGC-27) and normal cells (GES-1) were cultured in RPMI1640 added with 10% FBS and 1% penicillin-streptomycin. Quantitative real-tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Other evidence has shown that miR-let-7c-5p inhibits the proliferation and migration of cervical carcinoma cells [ 26 ] and negatively regulates NLRC5 protein expression in ethanol-induced hepatic injury [ 27 ]. Interestingly, miR-149-5p is capable of inhibiting the growth of gastric cancer, cholangiocarcinoma and glioblastoma [ 28 30 ]. MiR-149-5p can also inhibit M1 macrophage-associated inflammation in experimental abdominal aortic aneurysm formation [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other evidence has shown that miR-let-7c-5p inhibits the proliferation and migration of cervical carcinoma cells [ 26 ] and negatively regulates NLRC5 protein expression in ethanol-induced hepatic injury [ 27 ]. Interestingly, miR-149-5p is capable of inhibiting the growth of gastric cancer, cholangiocarcinoma and glioblastoma [ 28 30 ]. MiR-149-5p can also inhibit M1 macrophage-associated inflammation in experimental abdominal aortic aneurysm formation [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The myoblast proliferation was promoted after miR-144-5p treatment, which was the opposite of what was found in gastric cancer cells, that miR-144-5p could inhibit the cell proliferation [ 24 ]; therefore, we believed that miR-144-5p promoted growth and displayed anti-cancer activities. As a member of the dipeptidyl peptidase 4 protein family, FAP has both dipeptidyl peptidase and endopeptidase activities, could modulate fibrinolysis, seems to mostly appear in many kinds of fibroblasts, and is essential for cell survival [ 26 ].…”
Section: Discussionmentioning
confidence: 77%
“…It has been reported that some miRNA families like miR-1 and miR-133 family were myogenic specific and could regulate myogenesis [ 21 , 22 ]. miR-144-5p as a member of miR-144, could target RANKL and suppress cytokines expression [ 23 ] and involve in circ_0006282/miR-144-5p/YWHAB axis [ 24 ], but no research has reported its role on myogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…In another study investigating the effects of circ_0006282 and miR-144-5p in gastric cancer, a regulatory network with YWHAB was observed. Notably, YWHAB was positively modulated by miR-144-5p expression (21). miR-542-5p, a predictive breast cancer biomarker, is correlated with poor patient survival when overexpressed in tamoxifen-treated ER + ve breast cancer and YWHAB is a downstream target of miR-542-5p (22).…”
Section: Introductionmentioning
confidence: 94%